2017
DOI: 10.1590/s1980-6574201700030017
|View full text |Cite
|
Sign up to set email alerts
|

Football coaches’ development in Brazil: a focus on the content of learning

Abstract: Aim: The aim of the study was to analyze the lifelong content of learning of coaches. Methods: Eight coaches inserted in an Elite Football Club participated. Rappaport Time Line and semi-structured interviews were used to obtain the data. The coaches' learning was organized according to the theory of Lifelong Learning. 1-4 Results: The coaches presented in their personal experiences, with their families and as athletes, content of learning such as "leadership development" and "formation of values". In professi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
38

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 22 publications
(49 citation statements)
references
References 26 publications
0
11
0
38
Order By: Relevance
“…Além da preocupação com a desmotivação dos atletas, os treinadores relataram que procuram formar cidadãos por meio do esporte. Nessa perspectiva, o Desenvolvimento Positivo de Jovens é uma proposta que orienta para uma formação pessoal e social por meio do esporte (Camiré et (Stoszkowski & Collins, 2016;Tozetto et al, 2017). Assim, é preciso que pesquisadores e profissionais trabalhem juntos para enfrentar os desafios da prática e ofereçam experiências positivas para os jovens por meio do esporte (MacDonald et al, 2010).…”
Section: Desafios Da Carreiraunclassified
“…Além da preocupação com a desmotivação dos atletas, os treinadores relataram que procuram formar cidadãos por meio do esporte. Nessa perspectiva, o Desenvolvimento Positivo de Jovens é uma proposta que orienta para uma formação pessoal e social por meio do esporte (Camiré et (Stoszkowski & Collins, 2016;Tozetto et al, 2017). Assim, é preciso que pesquisadores e profissionais trabalhem juntos para enfrentar os desafios da prática e ofereçam experiências positivas para os jovens por meio do esporte (MacDonald et al, 2010).…”
Section: Desafios Da Carreiraunclassified
“…A concepção da Aprendizagem ao Longo da Vida nos permite ampliar quais são as experiências significativas para potencializar o desenvolvimento dos treinadores (TOZETTO et al, 2017). A formação centrada no treinador não coloca no centro da aprendizagem o que é meramente aprendido, mas no que o sujeito está se tornando a partir da sua forma de fazer, pensar e sentir (JARVIS, 2006).…”
Section: O Processo De Formação Dos Treinadores No Futebolunclassified
“…The aim of these meetings with the specialists would be to regularly share information (reflective cards) and knowledge (training sessions) in a productive, fast, and precise way so the coach can reflect on the different points of view that can affect key decisions in the organization 18 . After taking courses after graduation, the coaches already have experience and can reflect deeply on their performance and the issues faced in their daily environments 3 . In another study, Belão, Machado, and Mori 4 , found that the coaches in their study showed more confidence after taking post-graduate courses and short-term courses specific to Rhythmic Gymnastics.…”
Section: "[…] Last Year I Had the Opportunity To Participate In A Coumentioning
confidence: 99%
“…The competitive sports environment requires high dedication from coaches, who need to be constantly learning, reassessing practices, making decisions, and reflecting in order to maintain and achieve their results and goals 2 . However, the formal coach education programs, with pre-defined content to be followed in classes do not seem to meet all particular demands that each coach has in this competitive context 3,4 . Cassidy, Jones, and Potrac 5 and Mesquita, Ribeiro, Santos, Morgan 6 , suggest that a negative aspect of the formal courses of instruction would be the distance between theory and practice in which coaches find difficulties in transferring the content taught in class to their daily environments.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation